Sex cord stromal tumor of ovary masquerading as polycystic ovarian syndrome - Jhirwal, Manisha; Shekhar, Shashank; Sharma, Charu; Tak, Apoorva (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Virilization is a portentous sign that suggests the possibility of an ovarian or adrenal neoplasm. Diagnosis may be delayed in some patients due to nonspecific symptoms and overlapping symptoms with that of polycystic ovarian syndrome (PCOS). However, it must be remembered that PCOS usually causes mild to moderate elevation of serum testosterone with hirsutism whereas serum testosterone levels are many times elevated in cases of androgen secreting tumors and virilization is a norm. So high testosterone level with new onset virilization rule out PCOS. Authors are reporting two cases of Sertoli Leydig cell tumor despite their similar histopathology and equivalent levels of serum testosterone had a varied clinical spectrum of virilization.